THE ROLE OF MILD SEDATION AND/OR ANALGESIA IN THE NURSING CARE OF PATIENTS UNDERGOING PERCUTANEOUS CORONARY INTERVENTION. EMPHASIS ON BLOOD PRESSURE AND PATIENTS' PERCEPTIONS OF RESILIENCE AND SELF-COMPASSION. (June 2022) - Sarrou, Maria; Skoularigkis, Ioannis; Stougiannos, Pavlos; Trikas, Athanasios
Abstract : Objective: Percutaneous coronary interventions create stress and anxiety in patients, which usually affect blood pressure. Safe sedation is considered cornerstone therapy as relieves stress and pain. In chronic heart diseases the patient tries to negotiate the challenges of his illness which often aggravate his anxiety. The patient experiences the inability to manage and respond to others and/or his expectations, and as a result he "hurts" himself mentally. Self-compassion and self-esteem contribute to resilience. Resilience is a protective psychological factor in heart diseases. Purpose: The purpose of the research is the nursing monitoring and recording of the effects of the administered mild sedatives or analgesia during a percutaneous coronary intervention and the patients' perception of the care provided. Materials & Method: Questionnaires were used, answered by cardiac patients undergoing percutaneous coronary interventions (coronary angiography and angioplasty). The sample of participants is 100 people, where the 50 received midazolam (Dormixal) and fentanyl (Fentanyl) (group 1) five minutes before the examination and the remaining 50 did not (group 2). Blood pressure was measured and recorded before the start of the procedure, during, and at the end of it, in both groups to investigate a possible effect of the treatment. Design and method: During those three periods, there was a significant change in blood pressure (decrease) after the procedure in group 1 (120.76. 10.75 versus 129.86 ± 22.26 in group 2, p = 0.007). In group 1 the self-compassion scale was significantly and negatively correlated with the STAI scale and positively with the Connor scale. Those with a moderate financial level were less resilient while those with a high financial level showed less stress. Results: The majority of studies use these medications based on the adoption of the line "zero pain tolerance" in order to reduce or eliminate it. This difference is indicative of a possible effect of the treatment on the change (reduction) of blood pressure. In addition, it turns out that the higher the self-compassion, the greater the resilience and lower the stress